POR TRÁS DO PORTO HÁ A BARRA: REPERCUSSÕES DA ATIVIDADE PORTUÁRIA NA REGIÃO DE BARRA DO RIACHO EM ARACRUZ-ES - Oliveira, Bernardo Furlaneto Bragato Oakes de (2022)
This paper seeks to understand the magnitude of the impacts of port action on the community of Barra do Riacho in Aracruz - ES. Such an effort is undertaken by pointing out the centrality of the Portocel port complex and Aracruz Celulose in the development of extractive industrial and port activity in the region, making use of the sequestration of natural resources and expropriation of the traditional fishing community of Barra do Riacho. Through the historical presentation of the context based on a careful bibliographical and documental review, the work intends to confront the concreteness of the situation described with the critical theory of political economy and the Marxist, ecosocialist theoretical current, critically relating nexuses and general tendencies of contemporary capitalism observed in Aracruz.